1998
DOI: 10.1086/515315
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Transmission of Hepatitis C Virus from Human Immunodeficiency Virus Type 1‐Infected Mothers

Abstract: Antepartum plasma hepatitis C virus (HCV)RNA Hepatitis C virus (HCV) is the leading cause of chronic viralnently clears infection in õ30% of cases [5 -7]. This and the absence of an effective HCV vaccine underscores the imporhepatitis in the United States [1]. HCV infection may lead to cirrhosis, liver failure, and hepatocellular carcinoma [2 -4]; tance of reducing practices that enhance HCV transmission. HCV infection has been reported in 0% -30% of infants however, the only licensed treatment, a-interferon, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
113
3
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(130 citation statements)
references
References 56 publications
6
113
3
7
Order By: Relevance
“…Although mother-to-infant transmission occurred across a wide range of maternal viral titers, in 9 studies statistically higher maternal viral titers corresponded to a greater tendency for mother-to-infant transmission 19,33,34,40,[42][43][44][45][46] ; in 9 studies there was no difference. 18,20,27,[35][36][37][38][39]41 Most studies reported mother-to-infant transmission at viral titers beyond the range of 10 5 to 10 6 copies/mL.…”
Section: Maternal Viral Titermentioning
confidence: 99%
“…Although mother-to-infant transmission occurred across a wide range of maternal viral titers, in 9 studies statistically higher maternal viral titers corresponded to a greater tendency for mother-to-infant transmission 19,33,34,40,[42][43][44][45][46] ; in 9 studies there was no difference. 18,20,27,[35][36][37][38][39]41 Most studies reported mother-to-infant transmission at viral titers beyond the range of 10 5 to 10 6 copies/mL.…”
Section: Maternal Viral Titermentioning
confidence: 99%
“…The transmission rate varied from 4 to 8 % among mothers without HIV coinfection; however, it increased to 17-25 % among mothers coinfected with HIV [137][138][139][140]. Breastfeeding was not significantly associated with transmission [141], and cesarean section did not decrease perinatal HCV transmission from mothers to infants [140].…”
Section: Mother-to-infant Transmissionmentioning
confidence: 99%
“…By the inclusion of more than 100 mother-infant pairs and the use of improved laboratory methods, a second generation of perinatal research has narrowed the estimate of vertical transmission frequency to 3% to 8%, and has shown the necessity of careful, repeated testing to diagnose infant HCV infection (Table 1). [1][2][3][4][5] The second generation of mother-infant research also suggests that certain factors may influence perinatal transmission (Table 2). In 1999, the importance of each putative cofactor remains controversial, largely because studies have had too few participants to assess cofactors or their interactions.…”
mentioning
confidence: 99%
“…[2][3][4][5]8 Whether this represents false-positive enzyme immunoassay results (in studies done without immunoblot confirmation), intermittent viremia, or resolved infection, it is reasonable to reassure pregnant women in whom HCV RNA cannot be detected by sensitive tests that the transmission risk is exceedingly low. This finding also suggests that effective antiviral treatment could reduce HCV mother-infant transmission as it has with HIV.…”
mentioning
confidence: 99%
See 1 more Smart Citation